Manufacture and Characterization of Mucoadhesive Buccal Films Based on Pectin and Gellan Gum Containing Triamcinolone Acetonide - Felipe Pereira Fernandes; Amanda Campos Fortes; Said Gonsalves da Cruz Fonseca; Jörg Breitkreutz; Humberto Gomes Ferraz (International Journal of Polymer Science)
The treatment of canker sores can be quite compromised by the short period of the drug in the place of action. In this context, there is a need to develop drug dosage forms that allow more contact with the oral mucosa providing prolonged drug release. Therefore, the aim of this work was to obtain and characterize buccal films based on pectin and gellan gum in order to evaluate the potential use of these natural polymers in the production of pharmaceutical dosage forms for controlled release of TA in the oral mucosa. Using a 23 full factorial design, eight formulations were prepared by solvent casting method. The raw materials and films were characterized using techniques such as FTIR, DSC, and TG. In addition, thickness, mechanical properties, mucoadhesive strength, swelling, drug content, and dissolution profile of the films were evaluated. The results of FTIR, DSC, and TG showed that new chemical species are not formed in the production of films, and that these dosage forms have an adequate thermal behavior. All formulation showed a high degree of swelling, good mechanical resistance and elasticity, and a good mucoadhesive strength as well as able to act as a controlled release system.